Thermodynamic properties of methyl 4-(4-methoxyphenyl)-6-methyl-2-oxo-1,2,3,4-tetrahydropyrimidine-5-carboxylate in organic solutions - Ridka, O.; Matiychuk, V.; Sobechko, I.; Tyshchenko, N.; Novyk, M.; Sergeev, V.; Goshko, L. (Київський національний університет імені Тараса Шевченка, 2019)
The enthalpy and the entropy of dissolution of methyl 4-(4-methoxyphenyl)-6-methyl-2-oxo-1,2,3,4-tetrahydropyrimidine-5-carboxylate in 2-propanol, ethyl acetate, acetonitrile, 2-propanone and benzene were determined from the temperature dependence of its solubility.The enthalpies and the entropies of mixing at 298 K were calculated taking into account the enthalpy of melting of the compound, determined via differential thermal analysis.The influence of the solvent on the solubility of the compound and on the corresponding enthalpy and entropy of mixing values was shown.
Keywords: dissolution enthalpy; enthalpy of mixing; enthalpy of melting; entropy of dissolution; entropy of mixing; entropy of melting